Spontaneous intracranial hypotension associated with pachymeningeal enhancement in a patient with systemic lupus erythematosus (SLE): an extremely rare presenting feature. Issue 2 (7th February 2019) - Radhakrishnan, Shrivarthan; Surendran, Deepanjali; Barathi, Deepak; Bammigatti, Chanaveerappa
Abstract : A 16-years-old girl presented to our institution with history of severe bilateral headache for 5 days associated with vomiting. She also had fever for 2 months without any localising symptoms and skin lesions for 1 month. Examination revealed erythematous rash over bridge of nose and ear lobes, ulcer over hard palate and tenderness of small joints of both hands. Systemic examination was unremarkable except for bilateral papilloedema. Investigations revealed anaemia, leucopenia and elevated erythrocyte sedimentation rate. Cranial imaging revealed diffuse pachymeningeal enhancement with subdural effusion. Lumbar puncture revealed no abnormal findings in cerebrospinal fluid except low opening pressure. Antinuclear antibody was 4+ with anti-Sm antibody positive. She was diagnosed to have spontaneous intracranial hypotension associated with pachymeningeal enhancement secondary to sy stemic lupus erythematosus. She showed dramatic improvement with steroid and azathioprine therapy. She continues to be asymptomatic after 2 years of follow-up.